CONTROL OF COCOA POD BORER AND PHYTOPHTHORA POD ROT USING DEGRADABLE PLASTIC POD SLEEVES AND A NEMATODE, Steinernema carpocapsae - Ade Rosmana; Merle Shepard; Prakash Hebbar; Anita Mustari (Indonesian Journal of Agricultural Science, 2010)
Cocoa pod borer (CPB; Conopomorpha cramerella) and Phytophthora pod rot (PPR; Phytophthora palmivora) are serious pest and disease on cocoa plantations in Indonesia. Both pest and disease have been controlled with limited success using cultural practices such as pruning, frequent harvesting, sanitation, plastic sleeving, and chemical pesticides. An experiment was conducted on cocoa plantings in Pinrang Regency, South Sulawesi during the wet season of 2008/09 to test the effect of pod sleeving (with transparent degradable and non-degradable plastic bags) and nematode application on CPB and PPR infestation. The nematode, Steinernema carpocapsae (10,000 active juveniles per pod) was sprayed three times at intervals of 10 and 20 days. Pod damage by CPB was observed at harvest time, while PPR disease incidence was evaluated every week until harvest time. Results showed that all pods in the field were infested by CPB as indicated in control samples. Pod sleeving using both non-degradable and degradable plastics significantly reduced pod damage by CPB, from 62.3% in the control treatment compared to 8.4% in the CPB treatment. A combination of pod sleeving and nematode application had a synergistic reduction of pod damage by CPB resulting in totally healthy pods. Pod sleeving with degradable and non-degradable plastics also reduced pod damage by PPR significantly. Pod sleeving with non-degradable plastic suppressed the disease incidence almost zero until 6 weeks after sleeving and the rate of disease incidence was 3.6% per week. However, with degradable plastic, the disease suppression was even longer (7 weeks after sleeving), indicating that the degradable plastic is more effective. Combination of sleeving and nematode application slightly increased PPR infection. Sleeved pods in general had lower rates of PPR infection compared to pods treated with nematode or untreated pods (control). In these two applications, the rate of disease incidence was 7.8% and 8.3% per week respectively. The study implies that biological control using entomopathogenic S. carpocapsae and degradable plastic sleeves are effective and environmentally-friendly to control C. cramerella and P. palmivora